Markers of lipid and protein peroxidation among Nigerian university students with dysmenorrhoea (2018)
Introduction: Oxidative stress has been associated with primary dysmenorrhea, but studies that have assessed multiple markers of peroxidation are scarce. This study investigated malondialdehyde (MDA), nitrotyrosine (3‑NT), and protein carbonyls (PrCarb) as markers of oxidative stress and antioxidant status by serum alpha tocopherol level in young Nigerian women with dysmenorrhea. Materials and Methods: In a case–control design, 45 female undergraduates who had had regular menses for at least six previous cycles were recruited consecutively from a university clinic as cases and 45 apparently healthy age‑matched counterparts in their hall of residences as controls. Serum levels of MDA, 3‑NT, and PrCarb were determined using standard methods, and the values were compared between cases and controls using Mann–Whitney U‑test and graphs. Results: Study participants’ ages range from 16 to 29 years (mean = 22.0 ± 3.1 years). Serum level of 3‑NT (45.89 ± 37.11 vs 21.27 ± 13.94 ng/mL) and MDA (0.75 ± 0.19 vs 0.45 ± 0.11 nmol/mL) was significantly higher in cases than controls. Plasma alpha tocopherol was significantly lower in cases (7.51 ± 1.95 μmol/L) than controls (8.98 ± 1.95 μmol/L). Conversely, PrCarb levels were not significantly difference between cases and controls. There were significant correlations between alpha tocopherol and 3‑NT (r = −0.285; P = 0.007) and MDA (r = −0.321; P = 0.002), whereas this relationship was not shown with PrCarb (r = −0.073; P = 0.496). Conclusion: Remarkable lipid and protein peroxidation observed in young Nigerian women with dysmenorrhea was accompanied by correspondingly low level of serum alpha tocopherol suggesting potential need for vitamin E supplementation.